2014
DOI: 10.2478/manment-2014-0038
|View full text |Cite
|
Sign up to set email alerts
|

The Strategic Dimension of the Dynamic Capabilities of Enterprises

Abstract: Summary The aim of this paper is to contribute to the debate on the concept of dynamic capabilities of enterprises and present of its principles from the perspective of strategic management. The paper starts with the presentation of importance of paradigms in strategic management. It is followed by the discussion of the concept of dynamic capabilities and of the strategic aspects of the concept of dynamic capabilities of enterprises

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 7 publications
0
9
0
1
Order By: Relevance
“…This interest is, to a large extent, a consequence of the importance of relationships between the strategic choices of environmental conditions, businesses, and institutions. For this reason, dynamic capabilities are the subject of research in many areas such as marketing and entrepreneurship, innovation management, logistics, and tourism (Kozak and Dogantan, 2017; Krzakiewicz and Cyfert, 2014; Lawson and Samson, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This interest is, to a large extent, a consequence of the importance of relationships between the strategic choices of environmental conditions, businesses, and institutions. For this reason, dynamic capabilities are the subject of research in many areas such as marketing and entrepreneurship, innovation management, logistics, and tourism (Kozak and Dogantan, 2017; Krzakiewicz and Cyfert, 2014; Lawson and Samson, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, although strategic flexibility is considered an organization's capability to identify major changes in its external environment [20], empirical studies reported controversial results regarding the relationship between strategic flexibility and firm performance. In other words, having strategic flexibility is not sufficient for gaining a sustainable competitive advantage [21] and the impact on firm performance is context-dependent [22,23]. Hence, further investigating the conditions under which dynamic capabilities can perform better is necessary [9,24] Many present studies neglected the fact that high-tech firms need to be strategically flexible to adapt to unanticipated situations and rapidly changing environments, while also optimizing their business processes to achieve operational efficiency [25].…”
Section: Introductionmentioning
confidence: 99%
“…A high level of inertia can cause a significant lack of agreement between the organization's results and expectations related to adapting to the conditions of a changing environment. In the aspect of the change process, the strength of inertia may vary depending on the life cycle stage, its size and complexity and dynamic capacity can be a tool to increase their competitiveness [61,62]. However, inertia can also have positive features for enterprises that too willingly adapt to the constant changes arising from the turbulent, rapidly changing environment [63].…”
Section: System Approach To Adaptabilitymentioning
confidence: 99%